2022
DOI: 10.1155/2022/1906580
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Planning of Sports Competition Based on Deep Neural Network

Abstract: Physical education curriculum has been paid more and more attention by teachers and parents, and having a healthy body is the foundation. School sports competition is also more and more concerned by major researchers, and scholars have produced in-depth research and analysis of sports competition results prediction because prediction results can better let teachers carry out appropriate sports training for students, so as to achieve the best learning effect. The construction of the prediction model and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…On the basis of the preliminary analysis of the specialized scientific literature and the peculiarities of young athletes' versatile monitoring, a system of traits and their categories for the intelligent prediction was developed [1,4,9,12,24,25]. The system was classified into 36 traits, each of which was ranked into 2-4 categories, in three main personal areas: 13 traits via hereditary data, 12 traits via sports space, and 11 traits via individual achievement (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the preliminary analysis of the specialized scientific literature and the peculiarities of young athletes' versatile monitoring, a system of traits and their categories for the intelligent prediction was developed [1,4,9,12,24,25]. The system was classified into 36 traits, each of which was ranked into 2-4 categories, in three main personal areas: 13 traits via hereditary data, 12 traits via sports space, and 11 traits via individual achievement (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The problem of sports selection at the early stages of young athletes' sports training, as the results of the present study showed, implies the search for regularities, and in the given case, the highest combination of traits by categories compared to the combination of indicators of the whole studied group [4]. It, in turn, comes to the task of ordering system features comparing the indicators of young wrestlers and output results in the form of predictive models based on big data analysis [15,25]. This technology is based on determining the so-called taxonomic distance, that is, the distance between points in the multidimensional space from the identified traits via hereditary data, sport space and individual achievements of young wrestlers [3,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interrelation of AI, VR, AR, and DV creates a comprehensive platform for sports performance analysis. AI serves as the backbone for data collection, advanced data analysis, enhanced video, and notational, time-motion, and wearable data analysis efficiency [2,25,61,94,98,105,106]. Powerful AI tools can be used for injury prediction and prevention, empowering analysts' work by increasing processing speed, and offering predictive analytics and real-time feedback.…”
Section: Discussionmentioning
confidence: 99%
“…However, AI's value extends well beyond data collection. Another strength lies in data processing and interpretation [25]. Modern data collection techniques often generate enormous volumes of data, beyond human capabilities to handle and digest.…”
Section: How Ai Can Contribute To Sports Performance Analysismentioning
confidence: 99%